2022
DOI: 10.31234/osf.io/xz5w9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the use of a dance-based exergame to enhance autistic children’s social communication skills in the home and school environments: a feasibility study.

Abstract: Autistic individuals often display social-communicative and emotional differences that can affect various aspects of daily living. Furthermore, autistic children are more likely to partake in sedentary activities than their neurotypical counterparts. Therefore, the present study assessed the feasibility and potential efficacy of a dance-based exergame for enhancing autistic children’s social communication skills in the home and school environments. A mixed method, within-subject, pre-test/post-test study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Some parents noted that the intervention was particularly acceptable and effective for children who might not typically be drawn to other PA opportunities. This finding is consistent with prior studies that have found high acceptability of exergames like Just Dance for youth with autism ( 38 ). Finding non-traditional opportunities for PA may be particularly impactful for autistic youth, who often resist participation in traditional group PA programs, which tend to be loud, chaotic, and focused on high-intensity PA ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some parents noted that the intervention was particularly acceptable and effective for children who might not typically be drawn to other PA opportunities. This finding is consistent with prior studies that have found high acceptability of exergames like Just Dance for youth with autism ( 38 ). Finding non-traditional opportunities for PA may be particularly impactful for autistic youth, who often resist participation in traditional group PA programs, which tend to be loud, chaotic, and focused on high-intensity PA ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interview recordings were transcribed and themes in the three domains (feasibility, acceptability, accessibility) were coded by a primary (WK) and secondary (DH) reviewer using a modified grounded-theory approach. In this approach, themes are inductively identified from interview responses, not deductively identified according to theory ( 38 ). The primary reviewer developed an initial codebook, which was used and added to by the secondary reviewer.…”
Section: Methodsmentioning
confidence: 99%